ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN DALAM MEMPERGUNAKAN JASA TRANSPORTASI PT. SOLO CENTRAL TAXI DI SURAKARTA - Utami, Setyaningsih Sri (Universitas Slamet Riyadi, 2009)
ABSTRACT To determine correct production volume a company needed is assorted of appliance which can be utilized to determine the production volume, one of the utilized by appliance break-even analysis. This analysis is utilized to know how big executed production volume in the company will be able to reach situation break-even. Wide determination of correct production will mean also company has strived more effective in exploiting available production factors. Keywords: production capacities, break even point, linear programming,